Imaging Recommendations for Diagnosis, Staging, and Management of Adrenal Tumors - Kandasamy, Devasenathipathy; Gulati, Ajay; Simon, Betty; John, Reetu; Goyal, Alpesh (Indian Journal of Medical and Paediatric Oncology, 2023)
Adrenal glands are affected by a wide variety of tumors apart from infective and inflammatory lesions and their noninvasive characterization on imaging is important for the management of these patients. Incidentalomas form the major bulk of adrenal tumors and differentiation of benign adenomas from other malignant lesions, especially in patients with a known malignancy, guide further management. Imaging is an integral part of management along with clinical and biochemical features. The cornerstone of clinical and biochemical evaluation of adrenal tumors is to determine whether the lesion is functional or nonfunctional. Computed tomography (CT) is considered as the workhorse for imaging evaluation of adrenal lesions. CT densitometry and CT contrast washout characteristics are quite reliable in differentiating adenomas from malignant lesions. CT is also the modality of choice for the evaluation of resectability and staging of primary adrenal tumors. Magnetic resonance imaging (MRI) has superior contrast resolution compared to other morphological imaging modalities and is generally used as a problem-solving tool. MRI chemical shift imaging can also be used to reliably detect adrenal adenomas. Ultrasonography (USG) is used as a screening tool that is usually followed by either CT or MRI to better characterize the tumor and it is not routinely used for assessing the resectability, staging, and characterization of adrenal tumors. Another important role of USG is in image-guided sampling of tumors. Fluorodeoxyglucose positron emission tomography-computed tomography and other nuclear medicine modalities are a valuable addition to morphological imaging modalities. Image-guided interventions also play an important role in obtaining tissue samples where diagnostic imaging is not able to characterize adrenal tumors. In the functioning of adrenal tumors, adrenal venous sampling is widely used to accurately lateralize the secreting tumor.
Keywords: adrenal adenoma; adrenal incidentaloma; computed tomography; chemical shift imaging; adrenal venous sampling